Hubungan Antara Dukungan Keluarga Dengan Kualitas Hidup Lansia Di Desa Gonilan Kecamatan Kartasura Kabupaten Sukoharjo - Al Khorni, Soif; Supratman, Supratman, SKM., M.Kes., Ph.D (2017)
ABSTRACT Background: Of the total elderly population in Indonesia, many elderly people who can not enjoy their old age and feeling desperate, because the incidence of health problems because of the lack of attention from the family. As many as 1 billion of elderly in the world or one of four elderly people to various diseases. In fact, it is estimated the number of elderly who suffer from the disease will increase to 1.6 billion by 2025. Elderly express their complaints about the lack of attention and care from family members that feel life is not worth it anymore. It is caused by many things, including the busyness of family members, poverty and low education levels of family members, the family did not want to be bothered with problems and diseases that commonly affects the elderly. Methods: The study is classified as a correlational study. The study used cross sectional design. The population under study is the whole of the elderly in the village Gonilan already registered in District Health Clinics Kartasura totaling 100 people. Sampling method is simple random sampling method. Collecting data using questionnaires and data analysis using statistical test of chi square.Result: The result of Statistical tests of chi square between family support with the quality of life of elderly domain 1 (physical) obtained yield was 0.026, with domain 2 (psychological) obtained yield was 0,046, with domain 3 (social) obtained yield was 0,020 and the domain 3 (environment) obtained yield was 0.029.Conclusion: There is a relationship between family support and quality of life of elderly physical domain with chis square value of 0.026, the psychological domain with chis square value of 0.046, the social domain with chis square value of 0,020 and domain environment with chis square in the village of 0,029 Gonilan district. Kartasura Kab. Sukoharjo. Keywords: elderly, family support, quality of life